Design storm unit hydrograph computer program - Templo, Pedro T. Jr.
The estimate of the design flood is one of the governing inputs for the selection and sizing of many infrastructures. While the design storm unit hydrograph approach is one of the most reliable method for the estimate of flood magnitude, its computation if done manually, is too tedious. A computer program should make the method usable to a number of practicing hydrologists.